Algebra: concepts and processes - Acelajado, Maxima J.; Beronque, Yolando B.; Co, Frumencio F. (Mandaluyong City, 2005)
This book entitled Algebra...Concepts and Processes (Third edition) is designed primarily to meet the needs of the students enrolled in College Algebra
Keywords: algebra